عصر حاضر کےتعلیمی نظام میں اخلاقی بنیادوں کی تنفیذ اور سیرت النبی ﷺ سے راہنمائی:ایک تجزیاتی مطالعہ: Guidance from Seerat un Nabi (PBUH) in application of moral foundations in contemporary educational systems:An analytical Study - Dr. Syed Muhamad Tahir Shah, (Seerat Studies, 2023)
Commencing with the command to read, Prophet Muḥammad (peace be upon him) was appointed to the position of a teacher. Excelling in this role, he was then designated as a messenger, tasked with acquiring and promoting knowledge. His approach to education and persistent efforts reflects that an important portion of his life was dedicated to the promotion and spreading of knowledge. Education remained supreme in his routine to form the foundations of his great revolution. The success of His educational revolution can be recognized, among other factors, to the fact that He rooted a lot of ethical values into the foundations of education and emphasized their promulgation. Islam considers knowledge not just the accumulation of information but a commitment to these ethical virtues also. Prophet (PBUH) forbade to hide the knowledge and declared the corruption in knowledge worse from the corruption in wealth. He advised to attain the required competency in the knowledge and discouraged the arrogance in education like every field of life. He stressed to be practical regarding the education and to get the beneficial knowledge forever. He taught to pray and focus on increasing the knowledge and to respect the mentors and teachers. He suggested to make the educational process as easy as can be and preached to adopt ethical and moral values in educational process. In the present era, where education has transformed into a routine and formal practice, failing to provide substantial benefits, ethical values, awareness and encouragement, these ethical and moral aspects of education have become extremely essential. Applying these ethical teachings can enhance the benefits derived from education within the current educational system. This article observes these ethical and moral teachings in the light of the Prophet's (peace be upon him) Seerah, teachings and examples through an analytical and comprehensive lens.